2016
DOI: 10.1587/comex.2015xbl0184
|View full text |Cite
|
Sign up to set email alerts
|

HPBW control of dipole antenna with frequency selective reflector using different size elements

Abstract: This paper proposes a reflector backed dipole antenna whose reflector is composed of frequency selective reflector (FSR) and the size of the FSR elements aligned in the both side columns is changed. Since the width of the frequency selective reflector, which is composed of an array of the frequency selective elements, is chosen discretely, it is difficult to design an arbitrary beamwidth of the reflector backed antenna because the beamwidth of the reflector backed dipole antenna can be adjusted by the size of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Reference [9] used simulation and experiments to show that a cylindrical EBG controlled with PIN diodes is able to act as azimuth beam steering. Also, K. Cho, et al demonstrated in their study the beamwidth of a dipole antenna with a frequency selective reflector using dual-frequency band elements [10]. From the abovementioned study examples, FSS and EBG are regarded as the promising technologies for next-generation base station antennas, for which many of the current antenna characteristics are altered.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [9] used simulation and experiments to show that a cylindrical EBG controlled with PIN diodes is able to act as azimuth beam steering. Also, K. Cho, et al demonstrated in their study the beamwidth of a dipole antenna with a frequency selective reflector using dual-frequency band elements [10]. From the abovementioned study examples, FSS and EBG are regarded as the promising technologies for next-generation base station antennas, for which many of the current antenna characteristics are altered.…”
Section: Introductionmentioning
confidence: 99%